Protection from experimental ventilator-induced acute lung injury by IL-1 receptor blockade. Issue 2 (27th September 2007) - Frank, J A; Pittet, J-F; Wray, C; Matthay, M A
Abstract : Background: Clinical studies have shown that injurious mechanical ventilation is associated with increased airspace and plasma levels of interleukin-1β (IL-1β); however, the potential therapeutic value of IL-1 inhibition in acute lung injury has not been thoroughly investigated. A study was undertaken to determine if IL-1 signalling is a necessary early event in the pathogenesis of experimental ventilator-induced lung injury. Methods: Mice deficient in IL-1 receptor type 1 (IL1R1) and rats treated with IL-1 receptor antagonist (IL-1Ra) were mechanically ventilated with high tidal volume (30 ml/kg) and the effect of IL-1 signalling blockade on the severity of lung injury was determined. Results: Permeability, as measured by radiolabelled albumin flux, was significantly lower in IL1R1 null mice than in wild-type mice during injurious ventilation (p<0.05). IL-1Ra significantly decreased protein permeability and pulmonary oedema in rats during injurious ventilation and also decreased airspace and plasma levels of the chemokine CXCL1 and airspace neutrophils. IL-1Ra decreased expression of NOS2 and ICAM-1 mRNA in whole lung. Bronchoalveolar lavage fluid levels of RTI40, a marker of type I cell injury, were 2.5 times lower following IL-1Ra treatment (p<0.05). In isolated type II pneumocytes, IL-1β reduced electrical resistance and increased transepithelial permeability. Conclusions: IL-1 contributes to alveolar barrier dysfunction in VILI by promoting lung neutrophil recruitment and by increasing epithelial injury and permeability. Because preserved alveolar barrier function is associated with better outcomes in patients with acute lung injury, these data support further testing of IL-1Ra for the treatment of acute lung injury.